Post-orogenic thermotectonic history of the Mount Buffalo region, Lachlan Fold Belt, Australia: evidence for Mesozoic to Cenozoic wrench-fault reactivation? - O'Sullivan, P.B; Belton, D.X; Orr, M (Tectonophysics, 2000)
The Early Devonian Mount Buffalo granite is exposed today as an inselberg at the dissected western margin of the southeastern highlands of Victoria Australia. It dominates a block of deeply incised, Ordovician turbidites that appears structurally isolated from the surrounding highlands. By treating these highlands as an elastic plate subject to flexure or warping, previous workers have proposed that this region of the Lachlan Fold Belt has experienced a relatively simple thermotectonic and landscape evolution history following shallow-level intrusion of the granite. However, results of apatite and zircon fission-track analyses from the granite indicate the occurrence of major, previously unrecognized, episodes of: (1) heating/burial prior to ∼246 Ma (Early Triassic), and prior to ∼70 Ma (Late Cretaceous); and (2) rapid cooling/denudation at some time between ∼246 and 220 Ma (Early to Late Triassic), and between ∼70 and 50 Ma (Late Cretaceous to Early Tertiary). While previous interpretations of the landscape history of the region suggest the prolonged, subaerial exposure of the granite following shallow crustal residence, our results clearly indicate this region of the Lachlan Fold Belt has experienced a dynamic post-Paleozoic history. Thus this new dataset forces a radical re-interpretation of the landscape evolution of the Mount Buffalo structural block, which has significant implications for our understanding of the Mesozoic and Cenozoic geomorphic and structural development of southeastern Australia. We therefore propose a model incorporating reactivation of wrench faults that may explain the complex thermotectonic history while accommodating the detailed observations of previous workers in this area.